(untitled) (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This research aims to find out how society globally prepares itself to face challenges, tolerance and belief values in interfaith marriages seen from the literature review. The stages in this research are the stages of identification, screening and eligibility for research data. Assisted by the publish on perish and vosviewer tools, 60 articles were obtained which were used in this research. There are 4 clusters produced, namelyCluster 1 (Red): in this cluster there are 13 items related to interfaith marriages and will be labeled "Marriage Rules with Different Cultures". Cluster 2 (Green): this cluster explains the label "Ethnic Acculturation in Marriage". Cluster 3 (Blue): This cluster is divided into 13 keyword items consisting of "Ethography in Marriage". Cluster 4 (Yellow): This yellow cluster consists of 7 keyword items, which will be labeled "Racist Actions against children of interfaith marriages". The implementation in this research isInterfaith marriages can involve various aspects that need to be carefully considered to ensure a healthy and harmonious relationship between partners. Exploring the relationship between mixed marriagesand marital stability can have implications for family dynamics and long-term relationship outcomes